Developments of cation-exchange by in situ electron microscopy. Issue 1 (1st January 2019) - Casu, Alberto; Falqui, Andrea
ABSTRACT: In the last two decades, the synthesis of inorganic nanostructures was boosted due to the impressive development of colloidal chemistry, which allowed obtaining a multiplicity of objects with finely regulated and uniform morphology, crystal structure and chemical composition. Moreover, different post-synthetic approaches further contributed to this development, one of the most used being cation-exchange, i.e . a method to partially or totally replace the cations of the starting ionic nanostructure. Meanwhile, transmission electron microscopy knew a new flourishing mainly due to the commercial availability of ultra-bright electron sources and spherical aberration correctors, whose combination permitted using very intense beams with concomitant point resolution better than 0.1 nm, and of ultrasensitive/ultrafast new electron cameras. In turn, these terrific improvements gave rise to an unprecedented progress of in situ electron microscopy, which consists of the live, direct observation over time of sample changes caused by external stimuli. Here we review how the in situ electron microscopy has been capable of promoting and imaging cation-exchange reactions at the solid state involving colloidal nanostructures, whose fast evolution during reactions in liquid would have made them otherwise not investigable. Graphical abstract: